Anaylysis of the stories "Muz Kongil" and "Yol" by Sotim Avaz - Atoboyeva Aziza Muhiddin qizi; Madaminova Dilnura Bahodir qizi (Genius Journals, 2023)
This article analyzes the stories "Muz Kongil" and "Yol" composed by Sotim Avaz, a child of the Khorezm individuals, additionally talks almost the pith of the story, composing aptitudes, and characters.
Keywords: Imaginative work; aesthetic composition; substance of imaginative work